Solve by completing the square:
-x+3x^2=-5
I just can't seem to figure out how to get the answer after you've completed the square. FYI the answer is x=(1/6)+-[(sqrt59)/6)i]
$\displaystyle 3x^2 - x = -5$-x+3x^2=-5
$\displaystyle x^2 - \frac{x}{3} = -\frac{5}{3}$
$\displaystyle x^2 - \frac{x}{3} + \frac{1}{36} = -\frac{5}{3} + \frac{1}{36}$
$\displaystyle \left(x - \frac{1}{6}\right)^2 = -\frac{59}{36}$
$\displaystyle x - \frac{1}{6} = \pm \frac{i \sqrt{59}}{6}$
$\displaystyle x = \frac{1 \pm i \sqrt{59}}{6}$